Inequality of Power and Gender Relations in Cases of Sexual Violence on Campus: a Study of Legal Philosophy - Aditya Yuli Sulistyawan; Suparno Suparno; Shefia Ariesta Fernanda; Robiah Adawiyah (Jurnal Wawasan Yuridika, 2022)
Sexual violence can occur anywhere and anytime, including in education, especially in universities. Harassment by lecturers to students and senior students to junior students is the case that happens frequently. Several cases prove an unequal relationship between the perpetrator and the victim. This research aims to change people's thinking about the use of power and prove the existence of power and gender equality in sexual violence on campus. The research method used is the philosophy of law research through a paradigmatic study approach by examining the critical theory et al. paradigm and the feminist jurisprudence with the specification of analytical descriptive research, secondary data types, and qualitative data analysis methods. Thus, it was found that sexual violence on campus was influenced by inequality between people in power and gender due to the influence of the patriarchal system and the imbalance of historical structures that led to the arbitrariness of the perpetrators.